Perspectives in company law and financial regulation: essays in honour of Eddy Wymeersch - Tison, Michel (Cambridge Univ. Press, 2009)
The European model company act project / Theodor Baums and Paul Krüger Andersen -- The societas privata Europaea : a basic reform of EU law on business organizations / Theo Raaijmakers -- Ius audicibus : the future of EU company law / Jaap Winter -- Free movement of capital and protectionism after Volkswagen and Viking Line / Jonathan Rickford -- Centros and the cost of branching / Marco Becht, Luca Enriques and Veronika Korom -- Towards the end of the real seat theory in Europe? / Michel Menjucq -- The commission recommendations of 14 December 2004 and of 15 February 2005 and their implementation in Germany / Marcus Lutter -- The Nordic corporate governance model : a European model? / Jesper Lau Hansen -- Stakeholders and the legal theory of the corporation / Peter Nobel -- The renaissance of organized shareholder representation in Europe / Stefan Grundmann -- In search of a middle ground between the perceived excesses of US style class actions and the generally ineffective collective action procedures in Europe / Douglas W. Hawes -- Some modest proposals to provide viable damages remedies for French investors / Marie-Claude Robert Hawes -- Pre-clearance in European accounting law : the right step? / Wolfgang Schön -- International standards on auditing and their adoption in the EU : legal aspects and unsettled questions / Hanno Merkt -- Corporate governance : directors' duties, financial reporting and liability : remarks from a German perspective / Peter Hommelhoff -- Some aspects of capital maintenance law in the UK / Dan Prentice and John Vella -- Luxembourg company law : a total overhaul / André Prüm -- Role of corporate governance reform and enforcement in the Netherlands / Joe McCahery and Erik Vermeulen -- Adoption of the European directive on takeover bids / Joëlle Simon -- Application of the Dutch investigation procedure on two listed companies : the Gucci and ABN AMRO cases / Levinus Timmerman -- Obstacles to corporate restructuring : observations from a European and German perspective / Klaus J. Hopt -- Protection of third party interest under German takeover law / Harald Baum -- Takeover defences' and the role of law : a Japanese perspective / Hideki Kanda -- Principle-based, risk-based regulation and effective enforcement / Eilis Ferran -- The Committee of European Securities Regulators and level 3 of the Lamfalussy Process / Niamh Moloney -- Market transparency and best execution : bond trading under MiFID / Guido Ferrarini -- The statutory authority of the European Central Bank and Euro-area national central banks over TARGET2-Securities / Peter O. Mülbert and Rebekka M. Wiemann -- Learning from Eddy : a meditation upon organizational reform of financial supervision in Europe / Howell E. Jackson -- The SEC embraces mutual recognition / Roberta S. Karmel -- Steps toward the 'europeanization' of US securities regulation, with thoughts on the evolution and design of a multinational securities regulator / Donald C. Langevoort -- The subprime crisis : does it ask for more regulation? / Friedrich Kübler -- Juries and the political economy of legal origin / Mark J. Roe -- The practitioner and the professor : is there a theory of commercial law? / Jean Nicolas Druey -- A short paean for Eddy / Ruben Lee
Keywords: Aufsatzsammlung; Festschrift; Internationales Recht; Unternehmensrecht